The impact of electric vehicles on the transportion setor - Marques, Pedro Mendes (2019)
Due to the continuous useage of fossil fuels we are almost reaching a point of no return with catastrophic consequences in terms of climate change. With this issue in mind some companies, specifically in the automotive industry, have decided to go green with several BEV fleets which are changing and forcing cities to adapt to these changes and to the new APV options appearing with the purpose of enhencing and facilitate the mobility inside the cities. In this sense, the present investigation aims to estimate the impact and changes in the portuguese transportation sector, as well to assess the customer perception and identify the decision-making factors of an electric vehicle. An online questionnaire was used as a mean to collect the higher and broader number of respondents and its analysis was performed based on a qualitative analysis, hypothesis testing and correlations. The results predict a growth of the APV in Europe and in Portugal along with average age of the Portuguese automotive car parc. It also expected a growth of the charging points infrastructure and the mobility options within the city. A BEV buyer usually considers itself as an ambitious person, seeking for new information about technology, sociable and always looking for ways to improve their life’s and considers the running costs of an EV to be lower than a conventional car. Moreover, the Price and Autonomy are the two most valued factors in an EV and the Brand and Technology the least.